2023
DOI: 10.22541/au.169609839.97787658/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of MicroRNAs in female and male human reproduction: A Narrative Review

mohadeseh khoshandam,
Mohadeseh Khoshandam,
Leila Naserpour
et al.

Abstract: The role of MicroRNAs in human reproduction is exciting, and probably these regulatory molecules have an essential role in reproductive function. Currently, the regulatory role of miRNAs in male and female reproduction needs to be clearly understood, with a considerable amount of controversial and contradictory data. A targeted review of high-quality studies published to date on miRNA patterns related to female and male reproduction to describe their role and relationship with infertility and update knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…miR-21 is another miRNA that has been implicated in the development of PCOS. 32 Studies have shown that the expression of miR-21 increases in the serum and granulosa cells of PCOS patients. Additionally, miR-21 has been shown to regulate the expression of genes involved in the insulin signaling pathway, which may contribute to insulin resistance in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 is another miRNA that has been implicated in the development of PCOS. 32 Studies have shown that the expression of miR-21 increases in the serum and granulosa cells of PCOS patients. Additionally, miR-21 has been shown to regulate the expression of genes involved in the insulin signaling pathway, which may contribute to insulin resistance in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%